Risk assessment for big data in cloud:security, privacy and trust - Yusof Ali, Hazirah Bee; Abdullah, Lili Marziana; Kartiwi, Mira; Nordin, Azlin (ACM Press, 2018)
The alarming rate of big data usage in the cloud makes data exposed easily. Cloud which consists of many servers linked to each other is used for data storage. Having owned by third parties, the security of the cloud needs to be looked at. Risks of storing data in cloud need to be checked further on the severity level. There should be a way to access the risks. Thus, the objective of this paper is to use SLR so that we can have extensive background of literatures on risk assessment for big data in cloud computing environment from the perspective of security, privacy and trust.